Vocational Guidance for Young Patients with Atopic Dermatitis: A Survey of Physicians' Opinions and Practices - Marie-Noëlle Crépy; Lynda Bensefa-Colas; François Aubin; Michel Simon; Angèle Soria (Medical Journals Sweden, 2022)
Abstract is missing (Short communication)